Mealtime dosing of a rapid-acting insulin analog reduces glucose variability and suppresses daytime cardiac sympathetic activity: a randomized controlled study in hospitalized patients with type 2 diabetes. Issue 1 (31st October 2018) - Kanamori, Takehiro; Takeshita, Yumie; Isobe, Yuki; Kato, Ken-ichiro; Misu, Hirofumi; Kaneko, Shuichi; Takamura, Toshinari
Abstract : Objective: Glucose variability induces endothelial dysfunction and cardiac autonomic nerve abnormality. Here we compared the effects of mealtime insulin aspart and bedtime insulin detemir on glucose variability, endothelial function, and cardiac autonomic nerve activity among Japanese patients with type 2 diabetes. Research design and methods: Forty hospitalized patients received either mealtime insulin aspart or bedtime insulin detemir treatment for 2 weeks. We assessed glucose variability indices, including M-value, SD of blood glucose level, and mean blood glucose (MBG) level. Flow-mediated dilation (FMD) of the brachial artery was measured as an index of endothelial function. Low-frequency power, high-frequency power, and the low-frequency to high-frequency power ratio (LF:HF ratio) derived via heart rate variability analysis using a Holter ECG were employed as indices of cardiac autonomic nerve function. Results: M-values and MBG levels showed a considerably greater decrease in the insulin aspart group than in the insulin detemir group (p=0.006  vs p=0.001); no change in FMD was observed in either group. Daytime LF:HF ratio significantly decreased in the insulin aspart group but not in the insulin detemir group. Total insulin dose at endpoint in the insulin aspart group was significantly higher than that in the insulin detemir group (p<0.001). Conclusions: Mealtime insulin aspart reduced glucose variability to a greater extent than bedtime insulin detemir in patients with type 2 diabetes. Despite the need for higher insulin doses, insulin aspart decreased daytime cardiac sympathetic nerve activity. These properties may subsequently help reduce cardiovascular risks. Trial registration number: UMIN000008369.